A Case of Pediatric Kyrle-Flegel Disease in a 6-Year-Old Yemeni Girl - Mohammad Ali Alshami; Mona Jameel Mohana (Disease and Health Research: New Insights Vol. 5, 2024)
Kyrle’s disease (KD) and Flegel’s disease (FD) are rare variants of primary perforating dermatoses, characterized by transepidermal elimination of abnormal endogenous materials. In 1916, the Austrian dermatologist Josef Kyrle described multiple hyperpigmented papules and nodules 5–10 mm in size with a central keratotic plug in a 22-year-old diabetic woman. On the other hand, Flegel disease is considered a genodermatosis with autosomal dominant inheritance, manifesting in the third to fourth decade of life, although it has been reported in patients as young as 13 years of age. We describe a 6-year-old Yemeni girl with a 2-year history of generalized asymptomatic, small, reddish-brown keratotic papules with a lenticular central keratotic plug. The patient exhibited the clinical characteristics of FD; i.e., generalized small lesions mainly over the face, trunk, and extensor surfaces of the extremities, rather than the large lesions typically observed in KD. Although these features are synonymous with FD, the histology of a punch biopsy was consistent with KD. The patient was otherwise healthy, and no family members had a history of similar diseases. The patient was diagnosed with KD-FD, owing to the manifestation of features associated with both diseases. This case supports the hypothesis that KD and FD are different manifestations or at least represent different stages of the same disease.